The Stability and Elasticity in Ta-Ti-V Medium-Entropy Alloys Using First-Principles Calculations - Hu, Wenqiang; Pan, Min; Huang, Zheng; Yang, Hongwei; Wu, Hao; Pan, Liu; Cao, Zelin; Zhao, Yong (Frontiers in Materials, 2021)
Due to the low neutron activity, the high thermal stability, and the good compression strength at elevated temperatures, medium-entropy Ta-Ti-V alloys have the application potential to be used in future nuclear engineering. According to experimental results, a special quasi-random structure (SQS) model and first-principles calculations are used to calculate the structural stability and the elasticity of the ternary single-phase body-centered cubic (BCC) Ta-Ti-V alloys with the compositions Ta24Ti14V16, Ta19Ti17V18, Ta16Ti21V17, Ta22Ti23V9, and Ta18Ti18V18. The mixing energy of five compositions is positive, which indicates that they are unstable at low temperature but stable at high temperature. Meanwhile, we predict the ability of elasticity in those five compositions, and the sequence of bulk modulus is Ta24Ti14V16 > Ta19Ti17V18 > Ta18Ti18V18 > Ta16Ti21V17 > Ta22Ti23V9 and ductility is Ta19Ti17V18 > Ta18Ti18V18 > Ta22Ti23V9 > Ta24Ti14V16 > Ta16Ti21V17. Additionally, the influence of the element content on elastic properties shows that the Ta content will increase the bulk modulus of the alloys, while Ti content decreases the bulk modulus. Higher V and Ti contents are beneficial to ductility, especially the V content. The higher Ta content will sharply reduce the ductility of the alloys. Our calculation has provided further theoretical mechanism for the Ta-Ti-V medium-entropy alloys (MEAs) preparation and development.